Advance in pediatric spinal cord injury - Jian Zheng; Guoxin Nan (Wiley, 2024)
Abstract The incidence rate of spinal cord injury in children is lower than that in adults, accounting for about 5% of all spinal cord injuries. Motor vehicle accidents are the main cause of spinal cord injuries in children. As the spine of children is still in the process of growth and development, the anatomical structure and biomechanics have unique characteristics, and its etiology, injury site, and clinical manifestations are different from those of adults. Misdiagnosis and delayed diagnosis can lead to severe spinal deformity and neurological complications. Children and adolescents with spinal cord injuries may suffer from lifelong disability, which will do great harm to children, families, and society. Early magnetic resonance imaging examination can effectively avoid underdiagnosis of spinal cord injury without radiographic abnormality and select appropriate treatment. In addition, it is also important to establish a family‐centered rehabilitation model to help the affected children reintegrate into society and achieve the goal of returning to normal life. This article reviews the etiology, epidemiology, clinical characteristics, complications, and treatment of spinal cord injury in children and adolescents.